Ethical Considerations of Including Gender Information in Open Knowledge Platforms - Lindsey, Nerissa; Kuriger Suiter, Greta; Hanselman, Kurt (KULA)

(untitled) (University of Victoria Libraries, 2022)
In recent years, galleries, libraries, archives, and museums (GLAMs) have sought to leverage open knowledge platforms such as Wikidata to highlight or provide more visibility for traditionally marginalized groups and their work, collections, or contributions. Efforts like Art + Feminism, local edit-a-thons, and, more recently, GLAM institution-led projects have promoted open knowledge initiatives to a broader audience of participants. One such open knowledge project, the Program for Cooperative Cataloging (PCC) Wikidata Pilot, has brought together over seventy GLAM organizations to contribute linked open data for individuals associated with their institutions, collections, or archives. However, these projects have brought up ethical concerns around including potentially sensitive personal demographic information, such as gender identity, sexual orientation, race, and ethnicity, in entries in an open knowledge base about living persons. GLAM institutions are thus in a position of balancing open access with ethical cataloging, which should include adhering to the personal preferences of the individuals whose data is being shared. People working in libraries and archives have been increasingly focusing their energies on issues of diversity, equity, and inclusion in their descriptive practices, including remediating legacy data and addressing biased language. Moving this work into a more public sphere and scaling up in volume creates potential risks to the individuals being described. While adding demographic information on living people to open knowledge bases has the potential to enhance, highlight, and celebrate diversity, it could also potentially be used to the detriment of the subjects through surveillance and targeting activities. In this article we seek to investigate the changing role of metadata and open knowledge in addressing, or not addressing, issues of under- and misrepresentation, especially as they pertain to gender identity as described in the sex or gender property in Wikidata. We report findings from a survey investigating how organizations participating in open knowledge projects are addressing ethical concerns around including personal demographic information as part of their projects, including what, if any, policies they have implemented and what implications these activities may have for the living people being described.